PENGARUH MEDIA PEMBELAJARAN GAMEKINDO (BOARD GAME MARI KELILING INDONESIA) TERHADAP HASIL BELAJAR KOGNITIF MATA PELAJARAN IPS KELAS VII-G SMP NEGERI 22 MALANG - Wijayanti, Titik; Adi, Khofifatu Rohmah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study seeks to evaluate the efficacy of the educational game-based learning medium Gamekindo on the cognitive learning outcomes of seventh-grade students in class VII-G at SMP Negeri 22 Malang, specifically in Social Sciences (IPS) concerning the topic of socio-cultural diversity in Indonesia.  This study is grounded in the subpar learning outcomes of IPS, attributed to monotonous and less participatory pedagogical methods.  The research employed a quantitative methodology utilizing a Nonequivalent Control Group Design, comprising two classes: VII-G as the experimental group (utilizing Gamekindo) and VII-B as the control group (employing traditional lecture methods).  A multiple-choice test served as the primary instrument to assess cognitive learning results via pretest and posttest evaluations.  The data processing results indicated a substantial rise in the posttest scores of the experimental group relative to the control group, with an average increase of 24.58 points and a significance value (p) <0.05.  The data suggest that the utilization of Gamekindo can markedly enhance students' cognitive learning outcomes.  Consequently, board game-based learning media has demonstrated efficacy in fostering a more engaging and significant educational environment, serving as an alternative for enhancing IPS learning methodologies in junior high schools.